Recurrence of Chronic Subdural Hematoma Is Independent of ABO Blood Type: A Retrospective Cohort Study - Ou, Yunwei; Yu, Xiaofan; Wu, Liang; Zhang, Dong; Liu, Weiming (Frontiers in Neurology, 2022)
Objective A previous study with a limited number of patients has shown that blood type A was a risk factor in the recurrence of CSDH. The primary objective of this study was to investigate the association between the recurrence of CSDH and ABO blood type based on a larger sample size. Methods The authors reviewed in-patients with symptomatic CSDH from August 2011 to August 2021. Hospitalization information and data on long-term outcomes and recurrence among these patients were gathered. For all clinical variables, numbers (percentages) and mean ± standard deviations were used for categorical and continuous variables, respectively. For intergroup comparisons, the χ2 test or one-way ANOVA was carried out. Multivariable logistic regression analyses were performed to identify the association between CSDH recurrence and blood types. Results We included 1,556 inpatients in this study. The recurrence rate of CSDH showed no differences among different blood types. In the multivariable logistic regression analyses, ABO blood type (A: OR, 1.064; 95% CI, 0.467–2.851, p = 0.793; B: OR, 0.682, 95% CI, 0.315–1.269, p = 0.164; AB: OR, 0.537, 95% CI, 0.426–1.861, p = 0.357) was not a significantly independent predictor of CSDH recurrence. Conclusions Our study demonstrated that ABO blood type was not a risk factor in the recurrence of CSDH. Thus, we should not pay too much attention to ABO blood type in terms of CSDH recurrence.